2020
DOI: 10.1155/2020/2714746
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Genes and Pathways Associated with Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) is the leading cause of severe, permanent vision loss among the elderly in the developed world. The cellular and molecular pathogenesis of initiation and development of AMD remain poorly delineated. The limited resources of the human AMD RPE/choroid tissues impeded the extensive study of the disease. To better understand the molecular and pathway changes in human AMD RPE/choroid tissues, we searched the literature and found three independent studies using high-throughput … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…By knocking down the genes and examining the pathways, they showed that the diagnosis and examination of FADS2 and ACAT2 in the early stages of the disease will help to improve the quality of treatments [ 60 ]. Zhang et al displayed that RHO, PDE6A, 3′,5′-cyclic-GMP phosphodiesterase, and G protein alpha pathways play a role in the development and intensification of AMD [ 61 ]. Also, the study by Su et al, which analyzed this database, eventually nominated hsa_circRNA7329/hsa-miR-9/SCD, where hsa_circRNA7329 is in line with AMD's development [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…By knocking down the genes and examining the pathways, they showed that the diagnosis and examination of FADS2 and ACAT2 in the early stages of the disease will help to improve the quality of treatments [ 60 ]. Zhang et al displayed that RHO, PDE6A, 3′,5′-cyclic-GMP phosphodiesterase, and G protein alpha pathways play a role in the development and intensification of AMD [ 61 ]. Also, the study by Su et al, which analyzed this database, eventually nominated hsa_circRNA7329/hsa-miR-9/SCD, where hsa_circRNA7329 is in line with AMD's development [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…All of them clustered into molecular pathways (mainly phototransduction-related mechanisms and inflammatory/immune response) that exacerbate the RPE damage and, thus, are relevant to the etiopathogenesis of AMD. 80,81…”
Section: Discussionmentioning
confidence: 99%
“…All of them clustered into molecular pathways (mainly phototransduction-related mechanisms and inflammatory/immune response) that exacerbate the RPE damage and, thus, are relevant to the etiopathogenesis of AMD. 80,81 As mentioned throughout the manuscript, epigenetic elements such as DNA methylation changes occur at level of anti-oxidant factors and genes involved in the regulation of proliferation; miRNAs modulate the expression of angiogenic factors; histone modifiers appear dysregulated in disease-relevant genes. 25,26,31,68,69 Such evidence of dysregulation of gene expression may also suggest a potential upstream role for the epigenetic modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, RHO, PDE6A, 3′,5′-cyclic-GMP phosphodiesterase, and G protein alpha have been identified as AMD-related genes by canonical pathway analysis using the Ingenuity Pathway Analysis database. [ 34 ] We additionally identified HSP90AA1 , PRPF19 , PSMD4 , PSMD8 , PSMA4 , CHEK1 , SF3B5 , CCT7 , PSMB5 , and PSMB6 as the top ten hub genes associated with AMD. Importantly, in both of the analyzed cohorts, these genes were mostly upregulated in AMD RPE samples compared to healthy control samples.…”
Section: Discussionmentioning
confidence: 99%